The Application of Solar Dryer Technology in Enhancing Rice Cracker Production in Kromengan Village, Malang - Dini Kurniawati; Thatit Manon Andini; Aini Alifatin; Fajar Ramadhani Anggara; Danu Faruq Miffah; Wisnu Ananda; Irvan Maulana (Jurnal Pengabdian Masyarakat, 2023)
Purpose: To enhance the production and competitiveness of small and medium-sized enterprises (SMEs) specializing in rice cracker production in Kromengan Village, Kromengan District, Malang Regency by implementing solar-powered drying technology. Method: The community service project was carried out in several phases, beginning with the design and development of the drying equipment. Subsequently, experimentation was conducted with variations in drying rack positions. This was followed by providing training on how to use the equipment. Experimental testing of the equipment was necessary to assess the effectiveness of the drying process using this technology. Practical Applications: The drying process with this equipment can achieve moisture levels approaching those obtained through direct sun drying. Optimal drying occurred on racks 1 and 2 due to the efficient penetration of sunlight into the drying equipment. Additionally, the use of this equipment helps maintain the cleanliness of rice crackers by preventing dust and other contaminants. Conclusion: The application of solar-powered drying technology in rice cracker production has the potential to significantly improve the drying process and product quality for SMEs in Kromengan Village. This technology offers a practical solution for enhancing the competitiveness of the rice cracker industry and ensuring product hygiene, ultimately contributing to the economic development of the local community.